2007
DOI: 10.1007/s00213-007-0940-7
|View full text |Cite
|
Sign up to set email alerts
|

Brain imaging study of the acute effects of Δ9-tetrahydrocannabinol (THC) on attention and motor coordination in regular users of marijuana

Abstract: These findings suggest that in regular marijuana users, the immediate effects of marijuana may impact on cognitive-motor skills and brain mechanisms that modulate coordinated movement and driving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 59 publications
1
26
0
Order By: Relevance
“…Nevertheless, a greater rCBF increase from pre- to post-smoking in the chronic compared to occasional user group has been found in thalamus and cerebellum. Regular cannabis users [40] underwent an 18 FDG-PET scan analysis while applying a virtual reality maze task after the administration of 17mg delta-9-THC or placebo. More virtual wall hits under delta-9-THC have been accompanied by an increased brain metabolism during task performance in the middle and medial frontal cortices and anterior cingulate, while a reduced metabolism was found in the occipital lobes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a greater rCBF increase from pre- to post-smoking in the chronic compared to occasional user group has been found in thalamus and cerebellum. Regular cannabis users [40] underwent an 18 FDG-PET scan analysis while applying a virtual reality maze task after the administration of 17mg delta-9-THC or placebo. More virtual wall hits under delta-9-THC have been accompanied by an increased brain metabolism during task performance in the middle and medial frontal cortices and anterior cingulate, while a reduced metabolism was found in the occipital lobes.…”
Section: Resultsmentioning
confidence: 99%
“…During the task, marijuana users showed significantly higher ACC activity compared to healthy controls [40]. Furthermore, an earlier onset of cannabis use was associated with more commission errors compared to late onset users concomitant with more focal clusters.…”
Section: Resultsmentioning
confidence: 99%
“…Marijuana (mainly dependent on the THC dose used) reduces visual scanning, orientation ability, divided attention and psychomotor performance (Weinstein et al, 2008;Ashton, 2001;Smiley, 1999). Ramaekers et al (2006) found that the proportion of observations showing impairment of cognition and motor control progressively increased as a function of serum THC in different tasks.…”
Section: Introductionmentioning
confidence: 98%
“…More specifically, both acute and chronic doses of THC have been shown to cause impairment in attention and motor coordination in a maze task in humans [49], inhibition of movement and basal ganglia neuronal activity in adult rats [43], decreased locomotor activity in rats [51], and impaired spatial and non-spatial memory in adolescent and adult rats and mice [8, 27, 31, 34]. These effects can become increasingly severe the earlier in life the individual begins to use marijuana [33, 34], and are often greater in adolescents than in adults [8].…”
Section: Introductionmentioning
confidence: 99%